Impacto do uso de simbióticos na microbiota intestinal de pacientes com neoplasia colorretal submetidos a tratamento cirúrgico: ensaio clínico randomizado. - Luísa Martins Trindade (2023)
Surgery is often used to treat colorectal cancer (CRC). Patients undergoing major operations, such as intestinal resections, demonstrate an increased risk for the development of intestinal dysbiosis. The administration of biotherapeutic agents, such as the symbiotic, can maintain intestinal homeostasis, modulate the immune system, and, consequently, reduce the risk of complications. Thus, the present study aimed to evaluate the impact of preoperative symbiotic supplementation on the intestinal microbiota of patients with colorectal cancer undergoing surgical treatment. Methods: This is a unicentric parallel triple masked randomized clinical trial, carried out at the Hospital das Clínicas of the Federal University of Minas Gerais. The study included patients diagnosed with CRC, candidates for tumor resection surgery, of both sexes, aged ≥ 18 years, who agreed to participate and signed the Informed Consent Form. The study was approved by the Research Ethics Committee of the Federal University of Minas Gerais (CEP/UFMG), under process number CAAE 24375713.0.0000.5149 and registered in Clinical Trials under number NCT04874883. Patients were randomized to receive supplementation with symbiotic or maltodextrin (control), twice a day, for a minimum of four and a maximum of ten days. The patients allocated in the treatment group received the symbiotic Simbioflora® (commercial preparation containing 5.5g of fructooligosaccharides (FOS) added with four species of probiotic (Lactobacillus paracasei LPC-31; Lactobacillus rhamnosus HN001; Lactobacillus acidophilus NCFM; Bifidobacterium lactis HN019, at a concentration of 109 CFU per strain), while the patients in the control group received 6 grams of maltodextrin. In the pre- and postoperative periods, all patients underwent nutritional, anthropometric, food consumption, bowel function and complaints assessment. during hospitalization until discharge to investigate complications. In addition, feces were collected, before treatment (T1) and operation (T2) and, at hospital discharge (T3), to assess the intestinal microbiota and fatty acids of short chain (AGCC) During the operation, fragments of normal (TN) and tumor (TT) tissue were collected for evaluation of cytokine expression, mucus production and proliferation of the tumor marker Ki67. Statistical analyzes were performed using (Statistical Package for the Social Sciences for Windows Student) SPSS and PRISMA programs. The significance level adopted was 5%. Results: In all, 46 patients completed the study, 23 in the symbiotic group and 23 in the control group. Statistical similarity was identified between the groups, in the pre- and postoperative periods, in relation to general and clinical characteristics, as well as nutritional, anthropometric and food consumption status (p>0.05), except for protein consumption, which was higher in the symbiotic group at baseline (p<0.05). No statistical differences were identified between the two groups regarding the first evacuation, flatus elimination, digestive complaints, length of stay, postoperative complications and in-hospital mortality (p>0.05). However, the analysis of the intestinal microbiota of the feces collected in T2 showed a significant increase in the Firmicutes phylum, the Bacillaceae family and the Blautia genus after symbiotic supplementation compared to the control group (p<0.05). In addition, symbiotic supplementation contributed to the modulation of the intestinal microbiota of patients who did not have infectious complications (p<0.05). An increase in the Lachnospiraceae family and in the Faecalibacterium, Lachnospira, Clostridium, Bilophila, Slakia and Selenomomonas genera at T2 was identified in these patients (p<0.05). Greater production of butyrate in T2 and T3, and of acetate and propionate in T2, were demonstrated in the symbiotic group, compared to the control group (p<0.05). No significant differences were identified between groups in cytokine expression, TN mucus production and Ki67 expression (p>0.05). However, increased mucus production in TT was identified in the symbiotic group, compared with the control (p>0.05), as well as increased expression of Ki67 in the TN of both groups (p>0.05). Conclusion: The results of the present study demonstrated that preoperative symbiotic supplementation of patients with RCC undergoing tumor resection was able to modulate the intestinal microbiota, the production of SCFA and mucus, however, without repercussions on clinical outcomes.